👤

Find the p( 1 ) and p(–3) of each of the following polynomial function. Show solution.
[tex]1. \: \: p(x) = 3 {x}^{4} + 16 {x}^{3 } + 14 {x}^{2} - 24 {x}^{2} - 9[/tex]
[tex]2. \: \: p(x) = - {x}^{3} + 4 {x}^{2} + 7x - 11[/tex]
[tex]3. \: \: p(x) = {x}^{4} - 3 {x}^{2} - 1[/tex]

Please I need help


Sagot :

1. p(1) = 3(1)^4 + 16(1)^3 - 10(1)^2 - 9

=3 + 16 - 10 - 9

= 0

p(-3) = 3(-3)^4 + 16(-3)^3 - 10(-3)^2 - 9

=81 - 432 - 90 - 9

= -450

2. p(1) = (1)^3 + 4(1)^2 + 7(1) - 11

= 1 + 4 + 7 - 11

= 1

p(-3) = (-3)^3 + 4(-3)^2 + 7(-3) - 11

= -27 + 36 - 21 - 11

= -23

3. p(1) = (1)^4 - 3(1)^2 - 1

=1 - 3 - 1

= -3

p(-3) = (-3)^4 - 3(-3)^2 - 1

= 81 - 27 - 1

=53